Pre-diabetes, diabetes and predictors of incident angina among older women and men in the Cardiovascular Health Study. (January 2020) - Mathenge, Njambi; Fan, Wenjun; Wong, Nathan D; Hirsch, Calvin; Delaney, Chris (Joseph); Amsterdam, Ezra A; Koch, Bruce; Calara, Rico; Gardin, Julius M
Diabetes mellitus and angina pectoris are important conditions in older persons. The utility of pre-diabetes mellitus, diabetes mellitus and other risk factors as predictors of incident angina pectoris among older adults has not been characterized. We examined incident angina pectoris rates by sex and diabetes mellitus status in 4511 adults aged ⩾65 years without coronary heart disease at baseline from the Cardiovascular Health Study. Cox regression examined predictors of incident angina pectoris, including pre-diabetes mellitus or diabetes mellitus adjusted for sociodemographic characteristics and other risk factors, over 12.2 ± 6.9 years of follow-up. Overall, 39.1% of participants had pre-diabetes mellitus, 14.0% had diabetes mellitus and 532 (11.8%) had incident angina pectoris. Incident angina pectoris rates per 1000 person-years in those with neither condition, pre-diabetes mellitus, and diabetes mellitus were 7.9, 9.0 and 12.3 in women and 10.3, 11.2 and 14.5 in men, respectively. Pre-diabetes mellitus and diabetes mellitus were not independently associated with incident AP; however, key predictors of AP were male sex, low-density lipoprotein-cholesterol, triglycerides, systolic blood pressure, antihypertensive medication and difficulty performing at least one instrumental activity of daily living (all p < 0.05 to p < 0.01). In our cohort of older adult participants, while the incidence of AP is greater in those with diabetes mellitus, neither diabetes mellitus nor pre-diabetes mellitus independently predicted incident angina pectoris.